Alcohol consumption in India: a systematic review and modelling study for sub-national estimates of drinking patterns - Rastogi, Ankit; Manthey, Jakob; Wiemker, Veronika; Probst, Charlotte (Addiction, 2022)
Background and Aims In India, alcohol per capita consumption (APC) has substantially increased over the past 2 decades. Although consumption does vary across the country, consistent state-level data are lacking. We aimed to identify all state-level alcohol exposure estimates since 2000 to (i) model consistent current drinking (CD) (12 months) prevalence estimates for all 36 states/union territories (UT) in 2019 and (ii) compare state-level CD trends with national-level APC trends. Design A systematic review for studies on the Indian state-level prevalence of CD, lifetime abstinence (LA), alcohol use disorders (AUD) or the quantity of alcohol consumed among current drinkers (QU) was conducted. Subsequently, statistical modelling was applied. Setting Data were collected and modelled for all Indian states/UTs. Participants Studies since 2000 referring to the general adult population (≥15 years) of at least one Indian state/UT were eligible. The total sample size covered was 29 600 000 (males: females, 1:1.6). Measurements Results on LA, AUD and QU were summarized descriptively. For (i) the state-, sex- and age-specific CD prevalence was estimated using random intercept fractional response models. For (ii) random intercept and slope models were performed. Findings Of 2870 studies identified, 30 were retained for data extraction. LA, AUD and QU data were available for 31, 36 and 12 states/UTs, respectively. CD model estimates ranged from 6.4% (95% CI = 2.1%-18.1%; males) in Lakshadweep and 1.3% (95% CI = 0.7%-2.6%; females) in Delhi to 76.1% (95% CI = 68.1%-82.6%; males) and 63.7% (95% CI = 49.4%-75.7%; females) in Arunachal Pradesh. Over time, CD decreased in most states/UTs in the observed data, contradicting increasing national-level APC trends. Conclusions Alcohol use (measured as consistent current drinking) in India has large regional variations, with alcohol consumption being most prevalent in the North-East, Chhattisgarh, Telangana, Himachal Pradesh, Punjab and Jharkhand.